"Lugar de ser feliz não é supermercado" : a modernidade tardia em canções de Zeca Baleiro - Salvalaio, Ricardo Costa (2018)
The songbook by Zeca Baleiro is inserted between the end of the 20th century and the beginning of the 21st century and exposes some relevant themes of what Anthony Giddens (1991) calls "late modernity", such as the crisis of the self, consumerism, loneliness, technology, among others. In this sense, this work proposes to perform a literary analysis of some songs produced by the composer between 1997 and 2012, in order to show how the themes mentioned appear in Baleiro’s lyrics. At the same time, the songbook in question not only addresses important contemporary issues, but also values literacy and concern for the aesthetic dimension of the text, which will also be highlighted in the analysis. In this way, this work intends to identify, to confront and, mainly, to analyze the most important characteristics of the present society as they are staged in the songs of the composer from Maranhão, showing how his songbook converses with the time in which it was produced.